2003
DOI: 10.1074/jbc.m209389200
|View full text |Cite
|
Sign up to set email alerts
|

Sinorhizobium meliloti acpXL Mutant Lacks the C28 Hydroxylated Fatty Acid Moiety of Lipid A and Does Not Express a Slow Migrating Form of Lipopolysaccharide

Abstract: Lipid A is the hydrophobic anchor of lipopolysaccharide (LPS) in the outer membrane of Gram-negative bacteria. Lipid A of all Rhizobiaceae is acylated with a long fatty acid chain, 27-hydroxyoctacosanoic acid. Biosynthesis of this long acyl substitution requires a special acyl carrier protein, AcpXL, which serves as a donor of C28 (-1)-hydroxylated fatty acid for acylation of rhizobial lipid A (Brozek, K.A., Carlson, R.W., and Raetz, C. R. (1996) J. Biol. Chem. 271, 32126 -32136). To determine the biological f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
1
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(89 citation statements)
references
References 52 publications
(34 reference statements)
3
82
1
3
Order By: Relevance
“…However, although the lipid A component of S. meliloti LPS is bisphosphorylated (Gudlavalleti & Forsberg, 2003;Sharypova et al, 2003), we did not observe any differences in the membrane localization of 32 P i -containing lipids in the S. meliloti msbA2 insertional mutant relative to the parent strain (data not shown), suggesting that MsbA2 is not essential for the transport of either phosphorylated LPS or phospholipids. Consistent with this, we did not observe any altered sensitivities of the S. meliloti msbA2 mutant relative to the parent strain towards cell envelope disrupting agents usually associated with LPS mutants.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…However, although the lipid A component of S. meliloti LPS is bisphosphorylated (Gudlavalleti & Forsberg, 2003;Sharypova et al, 2003), we did not observe any differences in the membrane localization of 32 P i -containing lipids in the S. meliloti msbA2 insertional mutant relative to the parent strain (data not shown), suggesting that MsbA2 is not essential for the transport of either phosphorylated LPS or phospholipids. Consistent with this, we did not observe any altered sensitivities of the S. meliloti msbA2 mutant relative to the parent strain towards cell envelope disrupting agents usually associated with LPS mutants.…”
Section: Discussionmentioning
confidence: 56%
“…1B), providing further support that MsbA2 could be involved in the transport of a lipid-linked polysaccharide. Since previous studies have determined that the lipid A molecules of S. meliloti are modified with phosphate groups (Gudlavalleti & Forsberg, 2003;Sharypova et al, 2003), we labelled the lipid A and phospholipids of the S. meliloti parent and msbA2 : : pJH104t mutant by growth in the presence of 32 P i . However, analysis of the 32 P i -labelled lipids from either the inner-or outer-membrane fractions by TLC (data not shown), showed that disruption of the msbA2 gene was not affecting the membrane localization of the either the lipid A or phospholipids.…”
mentioning
confidence: 99%
“…Up to now, the most severe impairments in nodulation were reported in mutants deficient in O-chain (73,98). Significance of lipid A in symbiosis remains unclear because most of lipid A mutants show weak phenotypes such as delay and reduced competitiveness for nodulation (93,112) or sometimes no apparent symbiotic lesion (46,111). LPS may contribute to the establishment of symbiosis as a suppressor of plant defense responses because LPS from S. meliloti have been found to suppress defense responses in a host plant Medicago sativa cell culture induced by a yeast elicitor (1).…”
Section: Determinants Of Rhizobium Symbiosismentioning
confidence: 99%
“…The O-antigen is the most variable domain of the LPS, showing strain by strain diversity (35). LPS mutants of rhizobia exhibited extensive levels of symbiotic impairments ranging from complete lack of nodule formation (98), formation of non-nitrogen-fixing nodules devoid of bacteroids (73,74), nodules with less bacteroids and nitrogen fixation (17), abnormally developed bacteroids (19,85), delay in nodulation (50,93,112) to decreased competitiveness (31,50,93). Nevertheless, the majority of the LPS mutants can invade plant tissue more or less, suggesting that LPS is particularly important in later stage of symbiosis.…”
Section: Determinants Of Rhizobium Symbiosismentioning
confidence: 99%
“…In S. meliloti, several LPS biosynthesis genes have been identified, including lpsB, lpsCDE, lpsL, rkpK, and ddhB (10)(11)(12)(13)(14). The lpsB, lpsC, and lpsDE genes encode a type I glycosyltransferase, ␤-1,4-glycosyltransferase, and RfaG glycosyltransferases, respectively, which are involved in the biosynthesis of the core oligosaccharides.…”
Section: Ipopolysaccharide (Lps) Is Required Formentioning
confidence: 99%